IMPORTÂNCIA DA AUTOPSIA PSICOLÓGICA NA MEDICINA LEGAL E PSIQUIATRIA (REMUNOM, 2025)
Psychological autopsy is a retrospective investigation method essential for Legal Medicine and Forensic Psychiatry, aiming to reconstruct the psychological profile and mental state of an individual before death, especially in cases of equivocal deaths or suspected suicides. This article explores the conceptualization, foundations, and methodology of psychological autopsy, highlighting its relevance in determining the manner of death, differentiating suicide, homicide, and accident. Its applications in elucidating complex cases, the importance of collecting information from multiple sources (family, friends, medical records), and the analysis of personal documents are discussed. The role of psychological autopsy in psychiatric research on suicide is also addressed, contributing to the identification of risk factors and the development of prevention strategies. Finally, the methodological challenges, limitations, and ethical implications of this forensic practice are considered. Authors such as Genival Veloso França, Taborda, and Kaplan are referenced to support the discussion on the importance of this instrument in understanding deaths and advancing scientific knowledge.